2021
DOI: 10.3390/s21237858
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Integrated Solution for Monitoring and Protection of Power Supply System from Railway Infrastructure

Abstract: This paper describes an innovative integrated solution for monitoring and protection of the power supply system of electric traction. The development of electronics devices, new possibilities to communicate (wireless), and new sensors makes it possible to design, develop and implement new hardware–software structures in various fields such as energy systems, transportation infrastructure, etc. This contributes to increasing developments in the monitoring and protection of railway infrastructure. A monitoring a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…In this paper, the priority of the SVC operation is assigned to the current balancing before power compensation. Therefore, in each time period (1 sec), the best solution is selected from the Pareto front using (26).…”
Section: Simulation Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this paper, the priority of the SVC operation is assigned to the current balancing before power compensation. Therefore, in each time period (1 sec), the best solution is selected from the Pareto front using (26).…”
Section: Simulation Resultsmentioning
confidence: 99%
“…These factors may be changed during the day based on the parties' decisions. In (26), npop represents the number of population members. Due to real-time operation and for better convergence of the optimization algorithm, Equations ( 15)- (19) were used for generating the initial population in the decision space.…”
Section: Simulation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For a correct interpretation of the severity of the overtemperatures detected in infrared thermographic images, post-processing activities are required, which will calculate and compensate the temperatures identified in the elements of the investigated electrical equipment. At this stage, corrections will be made regarding the degree of electric current load of the investigated elements, as well as the level of wind influence in the case of outdoor investigations, (Andrusca et al, 2021), only after these final adjustments will the identified defect be correctly framed.…”
Section: Environmental Factor Considerations Within Infrared Monitoringmentioning
confidence: 99%
“…Some of them are caused by difficult environmental conditions, i.e., wide working temperature range from −50 °C (Siberian regions) to 85 °C, humidity, and even the risk of flooding in the Netherlands. Additionally, a train is powered up by high voltage (up to 25 kV [ 1 , 2 ]) and such a power line generates a huge electric field [ 3 ] which causes disturbances in the operation of electronic equipment. Train acceleration (as speed increases) also has an impact on the current observed [ 4 , 5 , 6 ] in the surrounding rail infrastructure.…”
Section: Introductionmentioning
confidence: 99%